Clinical "real‐world" experience with letermovir for prevention of cytomegalovirus infection in allogeneic hematopoietic cell transplant recipients. Issue 7 (19th April 2020) - Anderson, Anthony; Raja, Mohammed; Vazquez, Neisy; Morris, Michele; Komanduri, Krishna; Camargo, Jose
Abstract: Background: Letermovir was approved in 2017 for prevention of cytomegalovirus (CMV) infection in seropositive (R+) allogeneic hematopoietic cell transplantation (HCT) patients. Post‐marketing data with this new agent are scarce. Methods: We compared the incidence of both CMV reactivation (any viremia) and clinically significant CMV infection (CS‐CMVi; CMV DNAemia leading to preemptive treatment or presence of CMV tissue invasive disease) at days +100 and +200 post‐HCT in 25 adult allogeneic HCT patients who received letermovir prophylaxis (until day 100) and a historical control group of 106 CMV R+ allogeneic HCT recipients who underwent CMV preemptive therapy. Results: CMV reactivation within 100 days post‐HCT was lower in the letermovir group vs control group (20% vs 72% respectively, P  < .001). The 100‐day cumulative incidence of CS‐CMVi was significantly lower in the letermovir group vs control group (4% vs 59% respectively, P  < .001). Significantly reduced incidence of CMV reactivation and CS‐CMVi was also observed at 200 days in the letermovir group. No difference in mortality was observed between the two groups. Conclusion: This study confirms the efficacy of letermovir in preventing CMV reactivation in CMV R+ allogeneic HCT recipients in first 100 days post‐HCT and suggests sustained efficacy after discontinuation of prophylaxis.